2008
DOI: 10.1088/0022-3727/41/22/225404
|View full text |Cite
|
Sign up to set email alerts
|

The thermal effect on vibration of single-walled carbon nanotubes using nonlocal Timoshenko beam theory

Abstract: This paper is concerned with the use of the nonlocal Timoshenko beam model for free vibration analysis of single-walled carbon nanotubes (CNTs) including the thermal effect. Unlike the Euler beam model, the Timoshenko beam model allows for the effects of transverse shear deformation and rotary inertia. These effects become significant for CNTs with small length-to-diameter ratios that are normally encountered in applications such as nanoprobes. The elastic Timoshenko beam model is reformulated using the nonloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(67 citation statements)
references
References 54 publications
2
64
0
1
Order By: Relevance
“…It can be found that the critical stresses increase with the increase in temperature change at the same fluid velocity. This means that the nanobeam will be stiffer when it works under the low or room field [31,44]. It can be found in Eqs.…”
Section: Temperature Effects On the Critical Initial Stressesmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be found that the critical stresses increase with the increase in temperature change at the same fluid velocity. This means that the nanobeam will be stiffer when it works under the low or room field [31,44]. It can be found in Eqs.…”
Section: Temperature Effects On the Critical Initial Stressesmentioning
confidence: 98%
“…Murmu and McCarthy [29,30] studied the influence of longitudinal magnetic fields on the vibration of DWCNTs based on a nonlocal approach. Benzair et al [31] discussed the thermal effect on wave characteristics of SWCNTs, in which the exact nonlocal Timoshenko beam solution was presented.…”
mentioning
confidence: 99%
“…However, in most of these works, only the transverse vibrations of these structural elements have been investigated using different one-dimensional beam theories; see for example Refs. [1][2][3][4][5][6][7][8][9][10][11][12]. In some other works, the longitudinal vibration of these structural elements has been studied [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the lattice feature of the CNTs, traditional continuum mechanics is not applicable straightforwardly but the need for a continuum model is obvious especially for a substitution of the more expensive and less-flexible molecular dynamics (MD) model for CNT vibration simulation. There are already some vibration studies in this regard using the so-called Timoshenko beam theory [3][4][5] and the Eringen's nonlocal elasticity theory [6] where special constitutive relationship has been employed to replace the traditional strain and stress relation, hereafter referred to as the nonlocal Timoshenko beam theory. Hamilton's principle [7,8] and Flügge's shell theory [8,9] are two other approaches, which have resulted in some energy formalisms [7] for our reference.…”
Section: Introductionmentioning
confidence: 99%
“…The purposes of these investigations were to understand the effects of tube size, wavenumber, nanotube-lattice length, temperature-induced axial strain, and beam support nature, etc. on the CNT wave and/or vibration characteristics including phase speed, natural frequencies and/or mode shapes [3][4][5][8][9][10]. The primary objective was to find data to underlie future design and development of nanoelectromechanical systems (NEMS) devices [10].…”
Section: Introductionmentioning
confidence: 99%